Leksem "seksualizacja" w systemie polszczyzny i dyskursie publicznym 2019 roku = Lexeme "sexualisation" ["seksualizacja"] in the Polish language system and public discourse of 2019 - Szkudlarek-Śmiechowicz, Ewa (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The aim of the article is to show the lexeme "sexualisation" as as a contemporary Polish system's unit and its persuasive and manipulative burdens in media discourse. Lexeme, although present in the scientific, popular science and didactic discourses for years, was included in 2019 in the political discourse by conservative circles and - similarly to the lexeme "gender" - since has been used for persuasive and manipulative purposes. Emotional-axiological contextual conditions of the word are combined with the creation of a simplified vision of the world, based on simple dichotomous divisions of values and anti-values.
Keywords: korpus; dyskurs; słowa kluczowe; seksualizacja; gender; polska debata publiczna; corpus; discourse; keywords; sexualisation in Polish; gender in Polish; Polish public debate